2022
DOI: 10.1101/2022.04.29.490106
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phylogenomics provides insights into the evolution of cactophily and host plant shifts inDrosophila

Abstract: Cactophilic species of the Drosophila buzzatii cluster (repleta group) comprise an excellent model group to investigate genomic changes underlying adaptation to extreme climate conditions and host plants. In particular, these species offer a subject to study the transition from chemically simpler breeding sites (like prickly pears of the genus Opuntia) to chemically more complex hosts (columnar cacti). Here, we report four highly contiguous genome assemblies of three species of the buzzatii cluster. Based on t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 129 publications
(238 reference statements)
0
6
0
Order By: Relevance
“…Protein sequences encoded by single-copy genes were employed to build a species tree that showed the same topology as in recent phylogenomic studies of the repleta group (Moreyra et al, 2022) and the buzzatii cluster (Hurtado et al, 2019). Our estimation of GR using the BDI model, suggests an expansion of the OBP family in Drosophila.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Protein sequences encoded by single-copy genes were employed to build a species tree that showed the same topology as in recent phylogenomic studies of the repleta group (Moreyra et al, 2022) and the buzzatii cluster (Hurtado et al, 2019). Our estimation of GR using the BDI model, suggests an expansion of the OBP family in Drosophila.…”
Section: Discussionmentioning
confidence: 88%
“…Even though the range of variation of the OBP repertoire in Drosophilidae is not as wide as in other Dipteran families, we detected intra-specific variation within D. koepferae. Recent phylogenomic studies revealed that Bolivian and Argentinian D. koepferae diverged 0.3-0.7 My ago according to genomic data (Moreyra et al, 2019(Moreyra et al, , 2022. These currently allopatric populations are distributed in a geographic area that has been exposed to paleoclimatic changes that deeply affected the distribution of cacti.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations